IMPLEMENTASI APE, SOLUSI MELATIH PERKEMBANGAN MOTORIK, SENSORIK, DAYA FOKUS DAN KERJA SAMA (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2022)
Educational Game Tools (APE) are introduced to kindergarten students with the aim of reducing dependence on online games from gadgets that have been used in modern games. Children are at home when accessing the internet. APE can be used as a solution to train the development of focus, sensory, focus and cooperation of children during pre-school growth and development. The development of children's gross and fine motor sensors ranges from 2 to 5 years old, because preschool age is the most sensitive age for children, this age is the most strategic starting point for understanding the quality of children in the future. The aim of introducing APE is to reduce children's dependence on gadgets, especially for Kindergarten students R.A. Aisyah, Lancar Village, Larangan District, Pamekasan Regency. The method used is mentoring Kindergarten students by using APE namely colored balls. APE is suitable, good for use because children are more effective at learning to count, train motor skills, concentrate, recognize colors, speed and agility as well as train group/cooperation skills in completing games.